PENGARUH COMMUNICATION, RESOURCES, DISPOSITION, DAN BUREAUCRATIC STRUCTURE TERHADAP IMPLEMENTASI KEBIJAKAN PENDIDIKAN (Studi Kasus Pembentukan Dewan Pendidikan Kabupaten Tobasamosir) - Monang Sitorus1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
This paper describes and analyzes the influence of communication, resources, disposition, and bureaucratic structure on education policy implementation (a case study of Regency Tobasamosir Education Council). The policy implementation theory used in this research is derived from George C. Edwards III ( 1980) consisting of four variables: communication, resources, disposition, and bureaucratic structure. The research employs a survey method through a proportional sampling comprising 116 heads of household as respondents. The data are analyzed by using Path Analysis and LISREL ( Linear Structural Relation) 8.30 for windows. The result shows that: (a). the influence of communication ( X1) to education policy implementation (Y) is 0,63 (strong); (b) the influence of resources (X2) to education policy implementation (Y) is 0,52 (medium); (c) the influence of disposition (X3) to education policy implementation (Y) is 0,24 (low);and (d) the influence of bureaucratic structure ( X3) to education policy implementation (Y) is 0,47 (medium). The influence of independent variable X ( X1, X2, X3, X4) to Y is 0,58 (medium). After determination, the influence of X1, X2, X3, X4 to Y is 33,64%, and the other 65,36% is influenced by other factors (epsilon).